X=13/5 Y=6/5

because ,

2X - Y = 4 .....this is the first equation

3X + Y = 9.....this is the second equation

frome the first equation Y=9-3X then substitute this equation with the second equation

2X-(9-3X)=4

2X-9+3X=4

5X=13

X=13/5 then substitute this X in Y=9-3X

Y=9-3(13/3)

Y=(45-39)/5

Y=6/5

because ,

2X - Y = 4 .....this is the first equation

3X + Y = 9.....this is the second equation

frome the first equation Y=9-3X then substitute this equation with the second equation

2X-(9-3X)=4

2X-9+3X=4

5X=13

X=13/5 then substitute this X in Y=9-3X

Y=9-3(13/3)

Y=(45-39)/5

Y=6/5